Effect of Sunflower and Marine Oils on Ruminal Microbiota, In vitro Fermentation and Digesta Fatty Acid Profile - Vargas, Julio E.; Andrés, Sonia; Snelling, Timothy J.; López-Ferreras, Lorena; Yáñez-Ruíz, David R.; García-Estrada, Carlos; López, Secundino (Frontiers in Microbiology, 2017)
One study using the rumen simulation technique (RUSITEC) investigated the changes in the ruminal microbiota and anaerobic fermentation in response to the addition of different lipid supplements to a ruminant diet. A basal diet with no oil added was the control, and the treated diets were supplemented with sunflower oil (2%) only, or sunflower oil (2%) in combination with fish oil (1%) or algae oil (1%). Four fermentation units were used per treatment. RUSITEC fermenters were inoculated with rumen digesta. Substrate degradation, fermentation end-products (volatile fatty acids, lactate, gas, methane and ammonia), and microbial protein synthesis were determined. Fatty acid profiles and microbial community composition were evaluated in digesta samples. Numbers of representative bacterial species and microbial groups were determined using qPCR. Composition of the microbial community and diversity were based on T-RFLP spectra. The addition of oils had not effects on substrate degradation or microbial protein synthesis. Differences among diets in NDF degradation were not significant (P = 0.132), but the contrast comparing oil–supplemented diets with the control was significant (P = 0.039). Methane production was reduced (P < 0.05) with all oil supplements. Propionate production was increased when diets containing oil were fermented. Compared with the control, the addition of algae oil decreased the percentage C18:3 c9c12c15 in rumen digesta, and that of C18:2 c9t11 was increased when the control diet was supplemented with any oil. Marine oils decreased the hydrogenation of C18 unsaturated fatty acids. Microbial diversity was not affected by oil supplementation. Cluster analysis showed that diets with additional fish or algae oils formed a group separated from the sunflower oil diet. Supplementation with marine oils decreased the numbers of Butyrivibrio producers of stearic acid, and affected the numbers of protozoa, methanogens, Selenomonas ruminantium and Streptococcus bovis, but not total bacteria. In conclusion, there is a potential to manipulate the rumen fermentation and microbiota with the addition of sunflower, fish or algae oils to ruminant diets at appropriate concentrations. Specifically, supplementation of ruminant mixed rations with marine oils will reduce methane production, the acetate to propionate ratio and the fatty acid hydrogenation in the rumen.